Analisis Pengaruh Penghargaan, Lingkungan, serta Budaya Kerja terhadap Kinerja Pegawai melalui Displin Kerja sebagai Variable Intervening - Mahardika, Husein Satria; Satoto, Eko Budi; Cahyono, Dwi (BUDGETING : Journal of Business, Management and Accounting, 2023)
The purpose of this study is to reveal how to improve employee performance so that it is effective in improving work quality through the factors of appreciation, work environment, work culture and work discipline in BKPSDM Kab. Jember.. This research begins by developing a framework or research model between Awards, Environment, Work Culture, Work Discipline and Employee Performance. Furthermore, data was obtained from 105 respondents by distributing questionnaires through social media and consisting of open and closed questions. Respondents are employees of BKPSDM Jember. Then, the data obtained were analyzed quantitatively and structurally using Structural Equaition Modeling Method (SEM) using Partial Least Square version 07 program. In this study, it was found that awards have a significant positive effect on the work environment, work culture and discipline at BKPSDM. with direct and indirect path analysis. The conclusion of this study is that all the variables examined in this study have a positive and significant effect on improving the performance of BKPSDM Kab. Jember. Keywords: Islamic Work Ethic, Leadership Style, Motivation, Performance